Stability of Turoctocog Alfa, a Recombinant Factor VIII Product, during Continuous Infusion In Vitro - Takeyama, Masahiro; Nøhr, Anne Mette; Pollard, Debra (TH Open, 2020)
Objective Turoctocog alfa is a recombinant factor VIII (rFVIII) for the prevention and treatment of bleeding in patients with hemophilia A, including those undergoing surgery and invasive medical procedures. This in vitro study evaluated the physical and chemical stability of turoctocog alfa during continuous infusion (CI) over 24 hours at 30°C.Materials and Methods The study was performed at 30°C ( ± 2°C). A CI system with pump speed set at either 0.6 or 1.5 mL/h was used to evaluate the stability of three turoctocog alfa strengths (500, 1,000, and 3,000 IU), equating to doses of 1.1 to 16.1 IU/h per kilogram of body weight. The following parameters were evaluated at selected time points between 0 and 24 hours: appearance of solution, clarity, pH, potency, purity, content, total high molecular weight proteins (HMWPs), and oxidized rFVIII.Results The mean potency of turoctocog alfa was maintained within the predefined acceptance criteria during CI for both pump speeds with all three strengths at 6, 12, or 24 hours (500 IU: ≥484 IU/vial; 1,000 IU: ≥1,014 IU/vial; and 3,000 IU: ≥3,029 IU/vial). Furthermore, the appearance of solution, clarity, pH, purity, content of turoctocog alfa, total HMWP, and oxidized forms were also within the predefined limits, and comparable to the reference samples (time = 0 hours) for the pump speeds and product strengths assessed.Conclusion Physical and chemical stability of turoctocog alfa was maintained during CI over 24 hours. There was only minor degradation or changes in any of the parameters tested. Potency was within the prespecified acceptance limits throughout 24 hours of infusion. These findings confirm the suitability of turoctocog alfa for CI.
Keywords: continuous infusion; factor VIII; hemophilia A; potency; stability; turoctocog alfa